Mycobacterium tuberculosis H37Ra: a surrogate for the expression of conserved, multimeric proteins of M.tb H37Rv. Issue 1 (December 2016) - Boradia, Vishant; Patil, Pravinkumar; Agnihotri, Anushri; Kumar, Ajay; Rajwadi, Kalpesh; Sahu, Ankit; Bhagath, Naveen; Sheokand, Navdeep; Kumar, Manoj; Malhotra, Himanshu; Patkar, Rachita; Hasan, Navi; et al.
Abstract Background Obtaining sufficient quantities of recombinantM.tb proteins using traditional approaches is often unsuccessful. Several enzymes of the glycolytic cycle are known to be multifunctional, however relatively few enzymes fromM.tb H37Rv have been characterized in the context of their enzymatic and pleiotropic roles. One of the primary reasons is the difficulty in obtaining sufficient amounts of functionally active protein. Results In the current study, usingM.tb glyceraldehyde-3-phosphate dehydrogenase (GAPDH) we demonstrate that expression inE. coli orM. smegmatis results in insolubility and improper subcellular localization. In addition, expression of such conserved multisubunit proteins poses the problem of heteromerization with host homologues. Importantly the expression host dramatically affected the yield and functionality of GAPDH in terms of both enzymatic activity and moonlighting function (transferrin binding). The applicability of this system was further confirmed using two additional enzymes i.e.M.tb Pyruvate kinase and Enolase. Conclusions Our studies establish that the attenuated strainM.tb H37Ra is a suitable host for the expression of highly hydrophobic, conserved, multimeric proteins ofM.tb H37Rv. Significantly, this expression host overcomes the limitations ofE. coli andM. smegmatis expression and yields recombinant protein that is qualitatively superior to that obtained by traditional methods. The current study highlights the fact that protein functionality (which is an an essential requirement for all in vitro assays and drug development) may be altered by the choice of expression host.